Software metric evaluation on cloud based applications - Phani Sheetal, A.; Ravindranath, K. (International Journal of Engineering and Technology, 2017)
Unbound growth in the cloud computing service models have motivated the companies building traditional software to be migrated into the clouds. During the high demand of the traditional applications, the performance and quality of the software were evaluated by the popular and globally accepted metrics. Nevertheless, after the migration of the same applications into the cloud, the expectation and definition of performance and quality has been changed. The beneficiaries of these applications are setting new milestones for the applications. Hence, the recent demand of the research trend is to build new software metric models to match the trade of between the new expectations from the beneficiaries and the software quality policies for organization or individual or state. Thus this work makes an attempt to understand the traditional software quality metrics and try to justify the applicability of these parameters in the trend of cloud based software applications. This work also proposes a novel metric method for performance evaluation for the migrated applications into the cloud, with the intension of formalizing and standardizing the cloud based metric methods unlike the recent trends.